2019
DOI: 10.1097/wco.0000000000000663
|View full text |Cite
|
Sign up to set email alerts
|

Are high-frequency oscillations better biomarkers of the epileptogenic zone than spikes?

Abstract: Purpose of review Precise localization of the epileptogenic zone is imperative for the success of resective surgery of drugresistant epileptic patients. To decrease the number of surgical failures, clinical research has been focusing on finding new biomarkers. For the past decades, high-frequency oscillations (HFOs, 80-500Hz) have ousted interictal spikes-the classical interictal marker-from the research spotlight. Many studies have claimed that HFOs were more linked to epileptogenicity than spikes. This prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…The findings of ripples (80–280 Hz) and fast ripples (250–600 Hz) in epilepsy have drawn a great attention from the researchers. In comparison to previous reports ( Zijlmans et al , 2012 ; Mooij et al , 2017 ; Frauscher et al , 2018 ; Lee et al , 2019 ; Roehri and Bartolomei, 2019 ), the major novel finding is the quantitative measurements of kurtosis and skewness of VE signals in epilepsy. Though additional verification and validation are necessary, building on the present study, we consider it is possible to determine the abnormalities of HFBS by measuring the kurtosis and skewness of signals.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…The findings of ripples (80–280 Hz) and fast ripples (250–600 Hz) in epilepsy have drawn a great attention from the researchers. In comparison to previous reports ( Zijlmans et al , 2012 ; Mooij et al , 2017 ; Frauscher et al , 2018 ; Lee et al , 2019 ; Roehri and Bartolomei, 2019 ), the major novel finding is the quantitative measurements of kurtosis and skewness of VE signals in epilepsy. Though additional verification and validation are necessary, building on the present study, we consider it is possible to determine the abnormalities of HFBS by measuring the kurtosis and skewness of signals.…”
Section: Discussionmentioning
confidence: 67%
“…Though HFOs are a well-recognized biomarker for epilepsy research ( Frauscher et al , 2017 ), the average population data have not yet been shown to be applicable to diagnosis of a single patient ( Jacobs et al , 2018 ; King-Stephens, 2019 ). One barrier hindering HFOs from wide clinical applications ( Engel et al , 2009 ; Roehri and Bartolomei, 2019 ) is that the brain generates both epileptic (pathological) and physiological HFOs. Physiological HFOs can be divided into elicited (functional) and endogenous HFOs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This measurement is also confounded by the occurrence of physiological HFOs, which are associated with healthy cognitive processing [36]. The characteristics of physiological and pathological HFOs are not fully understood and may overlap with one another [37,38]. Lastly, the detection method and parameters can affect the measurement of HFO rate.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of a standardised and clear process to distinguish between pathologic and physiological oscillations has limited the use of this type of electrographic oscillations as a clinical biomarker (Roehri and Bartolomei, 2019). The difficulty of distinguishing between both is evident when trying to classify HFOs according to their spectral frequencies, as both physiological and pathological HFOs share a similar frequency band (Jones et al, 2000, Fink et al, 2015.…”
Section: Differentiating Between Physiological and Pathological Hfosmentioning
confidence: 99%